Alternanthera indica (Amaranthaceae), a new species from Kerala (India) - Arya, Sindhu; Iamonico, Duilio; Pino, Ivonne Sánchez-Del; Kumar, Venugopalan Nair Saradamma Anil (Phytotaxa, 2021)
A new species of Alternanthera from Kerala (SW-India), named Alternanthera indica, is described and illustrated. A detailed description, photographs, and drawings are provided. The new species resembles A. carcasana, A. paronychioides var. robusta, A. pungens, A. sessilis, and A. tenella for sharing habit and sessile synflorescences, but it differs from these species in several characters (i.e. shape and size of leaves, sepal length and hairiness, and appendages on the androecial tube margin and length).